Involvement of Doshas in Acid Peptic Disease - A Literary Review - Lini Grispin G,; Resmi B, (International Journal of Ayurveda and Pharma Research, 2021)
Doshas represent physiological activities going on continuously in our body. They form the elementary basis of living body along with Dhatus and Malas. A healthy state of body is maintained by the normal physiological equilibrium between Tridoshas. Any vitiation occurring to one among them can result in disequilibrium between Doshas and hence result in diseases. In the process of disease manifestation, not a single Dosha but all the three Doshas can get involved in varying degrees based on the Nidanas. The Doshas get aggravated due to various causes and produce different diseases by locating itself in various body parts. Therefore, one should understand a disease after examining the characteristics of a disease, its regional alterations and involvement of Doshadi nidanas. The literary review reveals that Acid Peptic Disease has more similarity to Amlapittta and all the three Doshas are involved in the manifestation of the disease. Vitiation of Pachaka pitta, Prana vayu, Samana vayu, Apana vayu and Kledaka kapha are evident and these are responsible for the manifestation of all the four diseases considered here viz. GERD, Gastritis, Gastric ulcer and Duodenal ulcer.